The structure of amyloid fibrils of the HET-s (218-289) prion as seen by solid-state NMR - Meier, Beat (Henry Stewart Talks, 2008)
3D structure is important, Prion hypothesis, Prions can form amyloids, Amyloids, Cross-beta arrangements give characteristic fiber diffraction patterns, Solid-state NMR can characterize amyloid fibrils, Atomic-resolution structure determination by NMR and x-ray, Distance information in NMR correlation spectra, The methodology to obtain 3D structures from solid (microcrystalline) samples has recently been developed, Structure determination is possible, Nevertheless, amyloids are different, Isotopic labeling allows to disentangle the intra/inter problem, HET-s: a functional prion, Structural information about HET-s (218-289) from earlier measurements, Chemical shift assignment, To go further we need distance restraints, Distance restraints for protein fibrils, Intramolecular restraints, Structure calculation, Structural features of the fibrils, Comparison with globular proteins
Archived at 2021/02/25